Different Gut Microbiomes of Developmental Stages of Field-Collected Native and Invasive Western Bean Cutworm, Striacosta albicosta, in Western Nebraska - Paul A. Ayayee; Austin Currie; Julie A. Peterson (Microorganisms, 2022)
While insects harbor gut microbial associates that perform various functions for the host, lepidopterans have not been considered as prime examples of having such relationships. The western bean cutworm, Striacosta albicosta (Lepidoptera: Noctuidae), is native to North America and has historically been a significant corn pest in its western distribution. It is currently expanding eastwards and is invasive in these new regions. Using 16S rRNA gene sequencing data, this study focused on characterizing the microbiota associated with field-collected eggs, larvae, adults, and host plant materials of S. albicosta in its native range. The diversity of microbiomes varied significantly among S. albicosta eggs, larvae, adults, and the host plant materials. Microbial diversity was highest in adult stages relative to other insect stages. Furthermore, S. albicosta eggs, larvae, and adults harbored very distinct microbial communities, indicative of stage-specific microbiomes possibly performing different functions. Bacterial taxa underscoring these differences in composition identified four phyla and thirty families across samples. Members of the Firmicutes (Unassigned Lactobacillales), Proteobacteria (Pseudomonadaceae and Moraxellaceae), Bacteroidota (Weeksellaceae), and Chloroflexi dominated across all developmental stages. In addition, cellulose-degrading Lactobacillales (phylum: Firmicutes) dominated larval microbiomes, indicative of larval plant diet. This taxon was comparatively negligible in eggs and adults. Members of Proteobacteria dominated egg and host leaf microbiomes, while members of Bacteroidota dominated nectar-feeding adult gut microbiomes. Our results suggest a possible diet-dependent stage-specific microbiome composition and the potential for using stage-specific microbes as potential biological control tools against this important pest moving forward.